Psychosocial Correlates of Jordanian Adolescents' Help-Seeking Intentions for Depression: Findings From a Nationally Representative School Survey. (April 2019) - Dardas, Latefa Ali; Silva, Susan G.; van de Water, Brittney; Vance, Ashlee; Smoski, Moria J.; Noonan, Devon; Simmons, Leigh Ann
Little is known about help-seeking for depression among Jordanian adolescents who are a vulnerable population with high rates of depressive symptoms and few mental health services. The purpose of this study was to (1) explore Jordanian adolescents' helpseeking intentions for depression and (2) examine whether depression stigma, depression severity, or their interaction are associated with Jordanian adolescents' willingness to seek help for depression and the type of treatment they would seek. In collaboration with the Jordanian Ministry of Education, we conducted a nationally representative, school-based survey of adolescents aged 12–17 years ( N = 2, 349). One fourth of the adolescents reported they would not seek professional help for depression, and those respondents had higher average depression scores. Among those adolescents willing to seek help, the most likely sources included family member (57%), school counselor (46%), psychiatrist (43%), religious leader (39%), and general health practitioner (28%). Lower stigma scores were associated with greater likelihood to seek psychotherapy or visit a psychiatrist, while higher stigma scores were associated with increased likelihood to seek help from a school counselor or a family member. Jordanian adolescents experience significant barriers to seeking professional help for depression. However, even among adolescents with greater depression severity and depression stigma, school counselors were identified as a key resource for help. These findings suggest that school-based interventions may fill a critical service need for adolescents with depression and other mental health problems. School nurses should be leveraged along with counselors to address mental health issues in this vulnerable population.